Effect of Soil Physical State on the Earthworms in Hungary - Marta Birkas; Laszlo Bottlik; Attila Stingli; Csaba Gyuricza; Márton Jolánkai (Applied and Environmental Soil Science)
Hungarian authors have long been discussing the role of earthworms in improving soil productivity. Earthworm counts in our higher quality soils are similar to those found in soils where more attention is paid to earthworm activity. Negative impacts that are independent of farming—such as sustained dry spells in the summer—also affect earthworm counts. Negative impacts that definitely depend on farming include land use causing soil moisture loss, deep stubble treatment leaving the soil without cover, and ploughing in the summer without subsequent pressing. The climate change is having both positive and negative impacts. Weather patterns are causing losses but adopting climate mitigating tillage are generating benefits. In the trials results so far show that tillage focusing on preserving soil moisture, structure, and organic materials, covering the surface in the critical months as well as adequate soil loosening are fundamental pre-requisites for making the soil a favourable habitat for earthworms.